SYNTHESIS OF SERIES CHEMICAL COMPOUNDS AND STUDYING OF THEIR APPLICATIONS (LIQUID CRYSTAL, THERMO-PHYSICAL), BIOLOGICAL ACTIVITY, COMPLEXATION WITH PB (II) - Aljamali, Nagham Mahmood; Sonba, Hayfaa Jassim; Kadhim Wasaf, Adhraa Abdul; Jaber Kadhum, Afaaq; Abed Alameer, Thanaa; Hadi Ridha, Sajida; Kadhum Ali, Seena (Innovare Journal of Sciences, 2016)
ABSTRACT Objective: Series new organic compounds were synthesized and identified in our paper via types of reactions represented by condensation reaction, alkylation reaction, and cyclization reaction. Methods: Preparation of many compounds through various reactions which studied several applications such as liquid crystal (LC), differential scanning calorimetry (DSC)-measurement, complexation with ion Pb, and other chemical studies such as conditions of complex. Results: The structure of the newly compounds were investigated using thin-layer chromatography-plate and many techniques (Fourier transforminfrared, H nuclear magnetic resonance, ultraviolet-visible, determination of optimal conditions, ratio of ligand:metal [L: M], molar conductivity measurements, some physical characterization) then studying the biological activity of compounds. 1 Conclusion: All compounds appeared application in LC, as ligands with lead ion Pb (II), it gave mole ratio of L:M (1:1) as a complex, they have been appeared high stability in DSC-measurements and gave good activity in biostudying against bacteria. Keywords: Liquid crystal, Differential scanning calorimetry, Azo, Schiff, Pb, Biological active, Formazan. Â 